Penetrating Keratoplasty for Keratoconus: Visual and Graft Survival Outcomes - Al-Mohaimeed, Mansour M. (Qassim University, Kingdom of Saudi Arabia, 2013)
OBJECTIVES: To evaluate the complications, and visual and graft survival outcomes in eyes that had undergone penetrating keratoplasty (PKP) for keratoconus. METHODOLOGY: This restrospective study includes 311 patients with keratoconus who had undergone PKP between January 1, 2001, and December 31, 2002, at King Khaled Eye Specialist Hospital. All patients were followed up postoperatively (maximum follow-up, 65.77 months). RESULTS: The mean age of patients with keratoconus at transplantation was 23.72 years. A preoperative best spectacle-corrected visual acuity (BSCVA) OF 20/40 or better was achieved in 13 eyes (4.2%). At a mean follow-up of 27 months, 212 eyes (68.2%) achieved a BSCVA of 20/40 or better. Postoperative visual acuity was significantly associated with preoperative visual acuity (P < 0.00). Only 6 eyes (1.9%) experienced graft failure, with a mean follow-up of 23.62 months. The graft rejection rate (6.8%) was a significant risk factor for failure (P = 0.00). Age, gender, corneal graft diameter, and intraoperative vitreous loss had no statistically significant effects on the PKP outcome (P> 0.05). Kaplan-Meier analysis revealed that the probabilities of graft survival were 99.8% at 1 year and 97.6% at 5 years after transplantation. CONCLUSION: Performing PKP in eyes with keratoconus is associated with good visual results and an excellent graft outcome.